Pedagogical Competency Gaps in the Implementation of Technological Pedagogical and Content Knowledge among Arabic Language Teachers in Indonesia and Its Implications for Learning Effectiveness - Ghulam, Maftukh; Firdausi, Anisah; Muhammad Thohir (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2026)
The rapid digital transformation in 21st-century education demands that Arabic language teachers master not only subject matter but also information and communication technology (ICT) integration. However, a significant gap persists in Indonesia between technological availability and effective pedagogical implementation, often hindered by traditional mindsets. Previous studies frequently focus on general ICT literacy or infrastructure, overlooking the specific intersection of technology and Arabic linguistics. This research aims to analyze the pedagogical competence imbalance within the TPACK framework and its implications for learning effectiveness. This study employs a qualitative approach with a library research and case study design. Field data collection was conducted through a systematic documentation technique of peer-reviewed journal articles, academic books, curriculum documents, and Arabic teacher training modules. Data analysis was processed through a multi-stage qualitative framework consisting of thematic data reduction, data display (matrix synthesis), and conclusion drawing/verification, with data trustworthiness ensured through source triangulation techniques . The results reveal a "pedagogical lag" where high technological knowledge is not synchronized with transformative instructional strategies, often resulting in superficial technology use that leads to student cognitive overload. In conclusion, bridging the pedagogical gap in TPACK is essential for meaningful instruction. The study recommends shifting teacher training toward subject-specific pedagogical technology to honor the richness of the Arabic language in the digital era.